Sodium-glucose cotransporter-1 inhibition and depression: A Mendelian randomization study - Gang Fan; Hong Zuo; Xun Shi; Bo Liu (SAGE Open Medicine)
Objective: The present study aims to determine the causal association between sodium-glucose cotransporter inhibitors and depression, as previous observational studies have concluded a potential link between sodium-glucose cotransporter 1/2 inhibition and depression. Methods: A total of 16 instrumental variables mimicking sodium-glucose cotransporter-1 inhibition and 6 instrumental variables mimicking sodium-glucose cotransporter-2 inhibition were selected for the study. Depression data from the Psychiatric Genomics Consortium and the UK Biobank ( n  = 500,199) was used as the primary outcome. We employed the random inverse variance weighted method as the primary Mendelian randomization analysis. Supplemental analyses were also conducted to ensure the robustness of the evidence. Results: Our results indicated that genetically predicted sodium-glucose cotransporter-1 inhibition was negatively related with depression risk (OR IVW  = 0.78; 95% CI: 0.67–0.91, p  = 0.002) in the European population. However, we did not find a causal association between sodium-glucose cotransporter-2 inhibition and depression (OR IVW  = 0.98; 95% CI: 0.71–1.36, p  = 0.919). Conclusions: The findings of this Mendelian randomization study indicate that sodium-glucose cotransporter-1 inhibition may decrease the risk of depression in the European population. Future studies must be done to clarify the mechanisms that underlie the causal relationship. Our study provides clear evidence of the potential benefits of sodium-glucose cotransporter-1 inhibition in depression.